Postpartum hemorrhage and pregnancy induced hypertension during emergency lower segment cesarean section: dexmedetomidine to our rescue - Uma Hariharan (Revista Brasileira de Anestesiologia)
Abstract Dexmedetomidine is a highly selective α-2 agonist which has recently revolutionized our anesthesia and intensive care practice. An obstetric patient presented for emergency cesarean delivery under general anesthesia, with pre-eclampsia and postpartum hemorrhage. In carefully selected cases with refractory hypertension and postpartum hemorrhage, dexmedetomidine can be used for improving overall patient outcome. It was beneficial in controlling both the blood pressure and uterine bleeding during cesarean section in our patient.